2019
DOI: 10.1002/per.2190
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Habitual Social Goals and Daily Well–Being: The Role of Age and Relationship Closeness

Abstract: There is a robust evidence that social approach goals (i.e. approach of positive social outcomes) have positive consequences and social avoidance goals (i.e. avoidance of negative social outcomes) have negative consequences for subjective well-being in young adulthood. Little is known about individual differences in social goals in later life. The current diary study with young (n = 212), middle-aged (n = 232), and older adults (n = 229) tested-and supported--the hypotheses that age (i) differentially predicts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…work, health, and social relationships), yet goal importance and especially goal attainability predicted later general and domain‐specific satisfaction rather similarly for adults of different age (Bühler et al, ). When differentiating social goals into approach and avoidance goals in very close, close, and peripheral social relationships, a more distinct pattern of associations with daily well‐being and satisfaction arose (Nikitin & Freund, ): Age‐related differences in social goals became most apparent in peripheral relationships compared to close relationships. Age differences in peripheral relationships are often explained with age‐related differences in remaining life time or future time perspective (Lang & Carstensen, ).…”
Section: Integrative Discussion Of Articlesmentioning
confidence: 99%
See 3 more Smart Citations
“…work, health, and social relationships), yet goal importance and especially goal attainability predicted later general and domain‐specific satisfaction rather similarly for adults of different age (Bühler et al, ). When differentiating social goals into approach and avoidance goals in very close, close, and peripheral social relationships, a more distinct pattern of associations with daily well‐being and satisfaction arose (Nikitin & Freund, ): Age‐related differences in social goals became most apparent in peripheral relationships compared to close relationships. Age differences in peripheral relationships are often explained with age‐related differences in remaining life time or future time perspective (Lang & Carstensen, ).…”
Section: Integrative Discussion Of Articlesmentioning
confidence: 99%
“…Changes in developmental tasks often co‐occur or necessitate environmental changes (e.g. changes in social relationships; Nikitin & Freund, ; Pusch et al, , and changes in daily situations; Müller et al, ; Noftle & Gust, ).…”
Section: Integrative Discussion Of Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although not predicted the relationship between avoidance motivation and positive affect is consistent with previous research on older adults. For example, Nikitin and Freund (2019a) found that avoidance goals in peripheral social relationships were positively associated with daily well-being in older (but not younger) adults. The authors argued that the positive association between social avoidance goals and daily well-being is driven by an age-differential adaptivity of social avoidance goals.…”
Section: Social Identity Threat Sense Of Belongingness and Social Motivationmentioning
confidence: 99%